Case-Based Reasoning Research and Development. 28th International Conference, ICCBR 2020, Salamanca, Spain, June 8-12, 2020, Proceedings (Lecture Notes in Computer Science, 12311, 2020)
This book constitutes the refereed proceedings of the 28th International Conference on Case-Based Reasoning Research and Development, ICCBR 2020, held in Salamanca, Spain*, in June 2020.